Kekuatan Hukum Perjanjian Sewa Menyewa Bangunan Tanpa Dasar Perjanjian Tertulis Ditinjau Pasal 1320 Jo Pasal 1548 Kitab Undang-Undang Hukum Perdata - oki yunice; Andreas Andrie Djatmiko; Ajar Dirgantoro (Yustitiabelen, 2023)
The purpose of this study is to determine the legal power of a building lease agreement without a written agreement based on it and the implementation of a building lease agreement in accordance with Article 1320 in conjunction with Article 1548 of the Indonesian Civil Code. The method and technique used in research to collect data through observation, interviews, and documentation is known as qualitative descriptive. Using the observation method, researchers obtain data about the actual condition of the rented building and the surrounding environment. The documentation method itself seeks data and conditions related to the object of research. The interview method is used to obtain direct information from sources to find out about the issues discussed in the study. Based on the results of the research, it can be concluded that the legal force regarding the building lease agreement without the basis of a written agreement and the implementation of the building lease agreement is related to the education and implementation of the agreement on leasing so that it is not against the law between the lessee and the lessee.